Pengaruh Gaya Hidup Terhadap Perilaku Keuangan Mahasiswa Fakultas Ekonomi Universitas Nias - Mendrofa, Aftitin Desti; Bate’e , Maria Magdalena; Harefa, Idarni; Zai , Kurniawan Sarototonafo (LPPM Universitas HKBP Nommensen, 2024)
Lifestyle is how a person behaves to allocate money and time which is expressed in activities, interests and opinions. Meanwhile, financial behavior is a person's ability to manage, namely planning, budgeting, checking management, controlling, searching and storing daily financial funds. As for the lifestyle of students at the Faculty of Economics, Nias University, which influences their financial behavior and how much influence lifestyle has on the financial behavior of students at the Faculty of Economics, Nias University. The research results show that: (1) Lifestyle has a positive effect on Financial Behavior. This is justified by the value of valid data processing results for Variables Therefore, the reliability test of these two variables can be declared reliable because the Cronbach Alpha value is above 0.6. (2) The correlation result with the SPSS software method is 0.919. This figure shows that the significant value is 0.919>0.05, which means that there is no correlation in this study. (3) The coefficient of determination of the R Square value shows a value of 0.844. If the percentage is at a value of 84%, this is the value of the Lifestyle variable that can be explained. (4) The results of the t test for variables X and Y processed in this research Ha are accepted and Ho is rejected, meaning that there is a significant influence of variable